Perilaku Pustakawan dalam Memberikan Layanan Turnitin di UPT Perpustakaan Universitas Muhammadiyah Makassar - Mirfayana Mirfayana; Quraisy Mathar; Wahyuni Ismail; Muh. Fakhruddin. S (Prodi Perpustakaan dan Sains Informasi, 2023)
This article discusses the behavior of librarians in providing Turnitin services and the behavior of librarians in responding to problems with Turnitin services. This research used descriptive qualitative research. The approach used in this research was a case study to examine a case in the context of the reality of life, including the behavior of librarians at the Unismuh Makassar Library Unit environment. Based on the research results, it was found that (1) the behavior of librarians at the Unismuh Makassar Library Unit found in this research includes aspects (a) attitude, (b) greeting behavior, (b) responding behavior, (c) disciplined behavior, (d) responsibility; and (2) How do librarians behave in responding to problems with Turnitin services at the Universitas Muhammadiyah Makassar Library Unit, including (a) Facility Constraints. The facility aspect was one of the obstacles found. This can be seen in the Turnitin service, which is still combined with other services due to limited space. and (2) User Constraints caused by users (students) taking Turnitin are pressed by the deadline for fulfilling graduation requirements. Another obstacle in this aspect is that users manipulate the Scientific Papers files that Turnitin will check. The research implies that librarians are required to improve service behavior with a positive image at the Universitas Muhammadiyah Makassar Library Unit and instill awareness in students about the importance of the originality of scientific work by providing advice, holding training, workshops, and seminars related to writing good scientific papers correctly or efficiently to reduce plagiarism results.